ANALISIS PERBANDINGAN ALGORITMA LZW DENGAN LEVENSTHEIN PADA KOMPRESI FILE PPT - Sihombing, Monalisa Dosma; Sunandar, Hery; Ulfa, Kurnia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In today's digital era, ppt or pptx files are crucial for presentations or data processing in the professional world. Using pptx for presentations allows for a more organized and structured presentation according to the design. However, the size of pptx files can be quite large compared to other data, leading to storage wastage. Thus, compression is needed. When compressing pptx files, it is important to balance file size and content quality. Higher compression levels reduce file size but may affect file quality. Data compression is a technique used to reduce file or information size without compromising data quality or significance. In an age of abundant data, data compression is essential for saving storage space and speeding up information transfer. By eliminating redundancy and utilizing existing data patterns, data compression can create a more efficient and compact representation. The challenge arises as pptx file sizes tend to be larger than other data due to the extensive use of slides, which wastes storage and slows down data transfer. To address this issue, a data reduction technique or compression is needed. Compression aims to reduce data size to a smaller size, and the compression parameters obtained include the ratio of compression, compression ratio, and space saving.